A psychometric study of the Russian-language version of the “Bayley Scales of Infant and Toddler Development–third edition”: An assessment of reliability and validity - Pavlova, Polina; Maksimov, Dmitry; Chegodaev, Dmitry; Kiselev, Sergey (Frontiers in Psychology, 2022)
Introduction. The Bayley Scales of Infant and Toddler Development - 3rd Edition (Bayley-III) is one of the most widely used tools for assessing child development, and adapted versions of this instrument have been successfully used in many countries. No comprehensive psychometric studies of the Bayley-III have yet been performed in Russia. Methods. This psychometric study was part of the longitudinal study conducted by the Ural Federal University in 2016–2020. Within the project, the original Bayley-III manual was translated into Russian and then used in a cohort of 333 infants to assess cognition, expressive/receptive communication, and fine/gross motor skills. For the purpose of psychometric analysis, we selected the data for four age groups of children from the longitudinal study database: 4–6 months (N=149), 10 months (N=138), 15 months (N=151) and 24 months (N=124). The development scores of the sample children were compared with the original Bayley-III norms in each age strata separately. Reliability and validity of the translated instrument were examined using correlation analysis, tests of internal consistency, and confirmatory factor analysis (CFA). Results. The average scaled scores of the examined children were generally comparable with the original (US) Bayley-III norms, with the exception of those older than one year, who demonstrated 1.2–1.9 points better performance in cognitive development and gross motor skills and 0.9–2.6 points lower performance in expressive communication. The correlation of both raw and scaled scores between different scales was low to moderate in all age groups (Spearman's ρ mostly within the range of 0.3–0.6; p < 0.001 for all pairwise correlations). Internal consistency tests confirmed high reliability of the translated instrument (Cronbach’s α=0.74–0.87, McDonald’s ω=0.79–0.89). CFA demonstrated a good fit of the three-factor model (cognitive, communicative, and motor components) in all age strata. Conclusion. The Russian version of the Bayley-III proved to be a psychometrically valid and reliable tool for assessing child development, at least in a research context. The development of the examined children was close to the original US norms, with some deviation in cognitive, gross motor and expressive communication scores mostly in older children, which could be attributed to the biased sample.